CLINICAL AND RADIOLOGICAL FINDINGS IN ARNOLD CHIARI MALFORMATION - Khan, Abdul Aziz; Bhatti, Sajid Nazir; Khan, Ghayyur; Ahmed, Ehtisham; Aurangzeb, Ahsan; Ali, Asghar; Khan, Amjad; Afzal, Saleem (Journal of Ayub Medical College Abbottabad, 2010)
Background: The Chiari Malformation I (CMI) is a disorder of uncertain origin that has been traditionally defined as downward herniation of the cerebellar tonsils through the foramen magnum. The anomaly is a leading cause of syringomyelia and occurs inassociation with osseus abnormalities at the craniovertebral junction. In contrast to other Chiari malformations, CMI tends to present in the second or third decade of life and is sometimes referred to as the '˜adult-type' Chiari malformation. The objective was to document clinical and radiological findings in Arnold Chiari Malformation-I. Method: This was a descriptive study carried out in Ayub Teaching Hospital Abbottabad at Neurosurgery Department during July 2008-July 2010. We examined a prospective cohort of 60 symptomatic patients. All patients underwent magnetic resonance imaging of the head and spine. Results: There were 40 female and 20 male patients. The age of onset was 24.9±15.8 years. Common associated radiological problems included syringomyelia (60%), scoliosis (25%), and basilarinvagination (12%), increased cervical lordosis 5 (8.5%), and Klippel Feil syndrome 2 (3.3%). The most consistent magnetic resonance imaging findings were obliteration of the retrocerebellar cerebrospinal fluid spaces (70% patients), tonsillar herniation of at least 5 mm (100% patients), and varying degrees of post fossa anomalies. Linical manifestations were headaches, pseudotumor-like episodes, a Meniere's disease-like syndrome, lower cranial nerve signs, and spinal cord disturbances in the absence of syringomyelia. Conclusion: These data support accumulating evidence that CMI is a disorder of the para-axial mesoderm that is characterised by underdevelopment of the posterior cranial fossa and overcrowding of the normally developed hindbrain. Tonsillar herniation of less than 5 mm does not exclude the diagnosis. Clinical manifestations of CMI seem to be related to cerebrospinal fluid disturbances (which are responsible for headaches, pseudotumor-like episodes, endolymphatic hydrops, syringomyelia, and hydrocephalus) and direct compression of nervous tissue. Keywords: Arnold Chiari Malformation, Posterior cranial fossa, Cerebrospinal fluid